Clinical research evidence of cupping therapy in China: a systematic literature review - Cao, Huijuan (BioMed Central, 2010)
BACKGROUND: Though cupping therapy has been used in China for thousands of years, there has been no systematic summary of clinical research on it. This review is to evaluate the therapeutic effect of cupping therapy using evidence-based approach based on all available clinical studies. METHODS: We included all clinical studies on cupping therapy for all kinds of diseases. We searched six electronic databases, all searches ended in December 2008. We extracted data on the type of cupping and type of diseases treated. RESULTS: 550 clinical studies were identified published between 1959 and 2008, including 73 randomized controlled trials (RCTs), 22 clinical controlled trials, 373 case series, and 82 case reports. Number of RCTs obviously increased during past decades, but the quality of the RCTs was generally poor according to the risk of bias of the Cochrane standard for important outcome within each trials. The diseases in which cupping was commonly employed included pain conditions, herpes zoster, cough or asthma, etc. Wet cupping was used in majority studies, followed by retained cupping, moving cupping, medicinal cupping, etc. 38 studies used combination of two types of cupping therapies. No serious adverse effects were reported in the studies. CONCLUSIONS: According to the above results, quality and quantity of RCTs on cupping therapy appears to be improved during the past 50 years in China, and majority of studies show potential benefit on pain conditions, herpes zoster and other diseases. However, further rigorous designed trials in relevant conditions are warranted to support their use in practice.